IMPLEMENTATION OF OCCUPATIONAL HEALTH AND SAFETY ON EMPLOYEES PRODUCTIVITY OF PRE-PRESS PRODUCTION DEPARTMENT AT PT NUSANTARA GRAFIKA - Tedi Ahmad Sugiarto; Yunus Fitriady (Politeknik Negeri Media Kreatif, 2019)
Every production process in a company can not be separated from all the dangers and risk of accident occupational. Therefore, in a company the need for Occupational Health and safety program to reduce and prevent work accidents. This observation aims to determine the application of Occupational Health and safety pre-press production section at PT Nusantara Grafika. This method of data collection are interviews, observations, and library studies. The object of observation that is labor in the Pre-Print section of PT Nusantara Grafika. Based on the results of this observation, the advice that can be submitted is that PT Nusantara Grafika should improves Occupational Safety and Health in the production area, especially pre-press parts so that the implementation of OHS is more effective.Keywords— Procedure, Productivity Value, Personal Protective Equipment, Pre-Press.